Pengaruh Penerapan Good Corporate Governance terhadap Tingkat Kesehatan dan Daya Saing di Perbankan Indonesia - Tobing, Adil; Arkeman, Yandra; Sanim, Bunasor; Nuryartono, Nunung (Jurnal Manajemen Teknologi, 2013)
The research aims to analyse contribution of Good Corporate Governance (GCG) implementation in Indonesia banking industry and its healthiness as well as its competitiveness. The research employs case study approach with the objects of State-owned Banks, which are Bank Mandiri, BRI, and BNI compared to Private Banks, which are BCA and Bukopin. Stepwise regression test are applied to find the correlation between GCG, healthiness, dan competitiveness, while Kruskall Wallis test is used to find whether any significant difference exists between the banks. The result shows that GCG implementation, based on the statistical methods, has significant relationship with the healthiness, which are inherent risk profile and capital adequacy variable, also with the competitiveness, which are productivity, profitability, and market valuation variable.Keywords : Banking Competitiveness, Banking Healthiness, Banking Performance, Good Corporate Governance (GCG), Private Banks, State-owned Banks